"Metformin-resistant" folic acid producing probiotics or folic acid against metformin's adverse effects like diarrhea. (September 2017) - Olgun, Abdullah
Abstract: Metformin, first line medication in the treatment of type2 diabetes by millions of patients worldwide, causes gastrointestinal adverse effects (i.e. diarrhea) in approximately 30% of patients, frequently leading to discontinuation. Interestingly, metformin was reported to increase life span in a microscopic worm, Caenorhabditis elegans, by decreasing folate and methionine production of bacteria that this worm uses as a food source. Metformin can be expected to have a similar effect on some microorganisms of human gut microbiota. This can disturb the balance of gut microbiota and cause gastrointestinal adverse effects by altering folate production of some types of bacteria and suppress their growth. Metformin resistant probiotics can be discovered or generated by artificial evolution/selection, and used to prevent these adverse effects. These patients can also be managed with folate supplementation.